Blackberry hacks - Mabe, Dave (Hacks series., 2005)
The BlackBerry has become an invaluable tool for those of us who need to stay connected and in the loop. But most people take advantage of only a few features that this marvelous communications device offers. What if you could do much more with your BlackBerry than just web surfing and email? BlackBerry Hacks will enhance your mobile computing with great tips and tricks. You'll learn that the BlackBerry is capable of things you never thought possible, and you'll learn how to make it an even better email and web workhorse: Get the most out of the built-in applications Take control of email with filters, searches, and more Rev up your mobile gaming--whether you're an arcade addict or poker pro Browse the web, chat over IM, and keep up with news and weblogs Work with office documents, spell check your messages, and send faxes Become more secure, lock down your BlackBerry and stash secure information somewhere safe Manage and monitor the BlackBerry Enterprise Server (BES) and Mobile Data System (MDS) Create web sites that look great on a BlackBerry Develop and deploy BlackBerry applications Whether you need to schedule a meeting from a trade show floor, confirm your child's next play date at the park, or just find the show times and secure movie tickets while at dinner, this book helps you use the remarkable BlackBerry to stay in touch and in-the-know--no matter where you are or where you go.